Hegemonic Masculinity in the Australian Defence Force – the Exclusion of Women from Combat Service as State Policy, 1973-2013 - Jericho, Jyonah (2015)
This thesis uses qualitative content analysis methods and aims to identify the dominant cultural and political themes elites seek to arouse when they defend Australia’s Gendered Combat Policy in the public domain. Male Defence personnel and Federal Government Ministers lead these discussions. No prior study explores how or why male elites and other men who benefit from hegemonic masculinity in state institutions actively defend the bio-political regime the Executive enforces over the gendered combat body. In recent decades, debates have shifted from away from criteria of gender to criteria of biology as public support for gender equality grows. Elites argue that the biophysical performance limitations of the female combat body justify the state enforcing this regime. Excluding women from combat duties is not just another case of discrimination against women that occurs in Australia’s work sector. The social problems that transpire from this policy extend beyond women’s diminished citizenship status. Excluding women from frontline military roles replicates the patriarchal makeup of key institutions of state power, locally and globally. The military is a formidable entity that defends Australia’s sovereignty and protects key institutions that uphold the state as a patriarchal construct. Excluding women from frontline military duties denies them the opportunity to accrue the experience required to lead Australia’s military institution locally and on the world stage. The absence of women in these senior roles is a dominant factor that upholds hegemonic masculinity within Australia’s civil–military relations and the realm of global warfare and international security. The exclusion of women from combat roles for over a century explains why Australia’s martial narratives and war images do not celebrate a feminised warrior archetype. This absence is a factor that replicates the way women are naturalised in passive roles that are subordinate to men in their nation’s collective consciousness